Asset Management. the Point of View of The Users` Costs - Almeida, José C. (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Bridges by their nature are structures that absorb a large amount of resources. For the promoter, usually public entities, the biggest share of the investment is made when the new structures are raised. However, as will be shown in the study presented in this paper, user costs are often much higher than direct costs and may even be higher by an order of magnitude. In addition to the costs resulting from maintenance/rehabilitation interventions, there are also environmental damages due to the pollution caused by the vehicles. The presented methodology will be applied to a case study where the global costs are highlighted and determined considering the scenario in which there are no disturbances in the circulation of vehicles and when they occur due to maintenance and rehabilitation works.
Keywords: sustainability; bridges; life cycle costs; maintenance costs; environment pollution; zrównoważony rozwój; mosty; koszty cyklu życia; koszty użytkownika; zanieczyszczenie środowiska